2018
DOI: 10.1007/s00277-018-3259-z
|View full text |Cite
|
Sign up to set email alerts
|

Blastic plasmacytoid dendritic cell neoplasm: update on therapy especially novel agents

Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and aggressive hematopoietic malignancy mainly affecting elderly patients. Most patients present with asymptomatic skin lesions as the first symptom and has a high frequency of bone marrow involvement. BPDCN is typically characterized by CD4+ and CD 56+ co-expression without common lymphoid or myeloid lineage markers. There is no consensus on the optimal therapeutic strategy for BPDCN. It is highly responsive to chemotherapy but the median event-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…Regimens for AML/ALL like hyper-CVAD, methotrexate and cytarabine, lymphoma chemotherapies like CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) and CHEOP (CHOP plus etoposide) may be effective 1 7 8 15 16. CNS prophylaxis using intrathecal therapy is highly recommended for BPDCN given the high risk of CNS involvement especially in relapses 1 7 8 15 16. Newer modalities include agents like venetoclax which is a BCL2 inhibitor effective in BPDCN 7 17.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regimens for AML/ALL like hyper-CVAD, methotrexate and cytarabine, lymphoma chemotherapies like CHOP (cyclophosphamide, doxorubicin, vincristine, prednisone) and CHEOP (CHOP plus etoposide) may be effective 1 7 8 15 16. CNS prophylaxis using intrathecal therapy is highly recommended for BPDCN given the high risk of CNS involvement especially in relapses 1 7 8 15 16. Newer modalities include agents like venetoclax which is a BCL2 inhibitor effective in BPDCN 7 17.…”
Section: Discussionmentioning
confidence: 99%
“…Two main patterns of presentation are ‘dermatopathic’ (>90%), with indolent skin lesions followed by tumour dissemination, and ‘leukaemic’, with systemic involvement from the very beginning 2. Although exceedingly rare, a number of sites of involvement have been reported in different case studies including bone marrow, lymph nodes, central nervous system (CNS), spleen, liver, lungs, pleura, mucosa of oral cavity, tonsils, paranasal sinuses, eyes, breasts, tongue, kidneys, muscles and even gall bladder 5–89…”
Section: Introductionmentioning
confidence: 99%
“…For the RUNX1 mutation, studies have revealed that in the adoption of a preclinical BPDCN mouse model, the combination of the classical demethylation drugs 5′‐azacytidine and decitabine resulted in effects of controlling disease progression, lead to a potential epigenetic inhibitor for RUNX1 mutation.…”
Section: Discussionmentioning
confidence: 99%
“…NGS revealed detailed information of RUNX1 mutation For the RUNX1 mutation, studies have revealed that in the adoption of a preclinical BPDCN mouse model, the combination of the classical demethylation drugs 5′-azacytidine and decitabine resulted in effects of controlling disease progression, lead to a potential epigenetic inhibitor for RUNX1 mutation7,8 .On the other hand, cladribine significantly modified the ratio of myeloid DCs to plasmacytoid DCs, B lymphocyte CD19 + cells have significantly decreased, and there were vital changes in CD4 + cells, CD8 + cells, and CD3 + , This population produced large amounts of interferon alfa (IFN-α), which could lead to the death of tumor cells.…”
mentioning
confidence: 99%
“…BPDCN is a rare and aggressive hematopoietic malignancy, which is highly responsive to chemotherapy treatment for ALL and not to CHOP therapy (cyclophosphamide, hydroxydaunorubicin, oncovin and prednisone) (4). Prior to starting treatment, patient was given a glucometer and advised to check blood glucose at least twice a day for close monitoring.…”
Section: Case Presentationmentioning
confidence: 99%